Rauwolfia vomitoria extract suppresses benign prostatic hyperplasia by inducing autophagic apoptosis through endoplasmic reticulum stress - Guifang Huang; Xiao He; Zesheng Xue; Yiming Long; Jiakuan Liu; Jinming Cai; Pengfei Tang; Bangmin Han; Bing Shen; Ruimin Huang; Jun Yan (BMC, 2022)
Abstract Background The current drug treatments for benign prostatic hyperplasia (BPH) have negative side effects. Therefore, it is important to find effective alternative therapies with significantly fewer side effects. Our previous study revealed that Rauwolfia vomitoria (RWF) root bark extract reversed BPH development in a rat model. However, the molecular mechanism of its inhibitory effects on BPH remains largely unknown. Methods BPH-1 and WPMY-1 cell lines derived from BPH epithelial and prostatic stromal compartments were selected to investigate how RWF extract inhibits BPH in vitro by MTT and flow cytometry assays. Microarray, quantitative real-time PCR, immunoblotting, and GFP-LC3 immunofluorescence assays were performed to evaluate the effects of RWF extract on endoplasmic reticulum stress (ER stress) and autophagic apoptosis pathways in two cell lines. A human BPH ex vivo explant assay was also employed for validation. Results RWF extract treatment decreased cell viability and induced apoptotic cell death in both BPH-1 and WPMY-1 cells in a concentration-dependent manner with the increase of pro-apoptotic PCDC4 protein. RWF extract induced autophagy by enhancing the levels of autophagic genes (ULK2 and SQSTM1/p62) and the LC3II:LC3I ratio, with the increase of GFP-LC3 puncta. Moreover, RWF extract activated PERK- and ATF6-associated ER stress pathways by inducing the transcriptional levels of EIF2AK3/PERK, DDIT3/CHOP and ATF6, accompanied by the reduction of BiP protein level, but not its mRNA level. Another ER stress pathway was not induced by RWF extract, as manifested by the lack of XBP1 splicing. Pharmacological inhibition of autophagy by 3-methyladenine abrogated apoptosis but not ER stress; while inhibition of ER stress by 4-phenylbutyrate alleviated the induction of autophagy and apoptosis. In addition, pretreatments with either 3-methyladenine or 4-phenylbutyrate suppressed RWF extract-induced cytotoxicity. Notably, the inductions of PERK- and ATF6-related stress pathways and autophagic apoptosis were confirmed in a human BPH ex vivo explant. Conclusions Our data have demonstrated that RWF extract significantly suppressed the viabilities of BPH epithelial cells and BPH myofibroblasts by inducing apoptosis via upregulating ER stress and autophagy. These data indicate that RWF extract is a potential novel alternative therapeutic approach for BPH.